2015
DOI: 10.1016/j.fct.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol from a candidate modified risk tobacco product has reduced effects on chemotaxis and transendothelial migration compared to combustion of conventional cigarettes

Abstract: Reduction of harmful constituents by heating rather than combusting tobacco is a promising new approach to reduce harmful effects associated with cigarette smoking. We investigated the effect from a new candidate modified risk tobacco product, the tobacco heating system (THS) 2.2, on the migratory behavior of monocytes in comparison with combustible 3R4F reference cigarettes. The monocytic cell line (THP-1) and human coronary arterial endothelial cells (HCAECs) were used to analyze chemotaxis and transendothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…For example, we have already leveraged the Apoe −/− mouse study to concomitantly evaluate the reduction potential of THS2.2 aerosol for cardiovascular endpoints ( Phillips et al , 2015b ). In another example, to evaluate a relevant mechanism of the CS-mediated cardiovascular effects (ie, atherosclerosis), we have compared the effects of THS2.2 and 3R4F on chemotaxis and transendothelial migration of a monocytic cell line ( van der Toorn et al. , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have already leveraged the Apoe −/− mouse study to concomitantly evaluate the reduction potential of THS2.2 aerosol for cardiovascular endpoints ( Phillips et al , 2015b ). In another example, to evaluate a relevant mechanism of the CS-mediated cardiovascular effects (ie, atherosclerosis), we have compared the effects of THS2.2 and 3R4F on chemotaxis and transendothelial migration of a monocytic cell line ( van der Toorn et al. , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous aerosol extract from IQOS has reduced effects on the adhesion of monocytic cells to human coronary endothelial cells compared to the aqueous reference cigarette smoke extract [55]. The aerosol extracts from IQOS were also found to induce less inflammation and migration, and to be less cytotoxic than those from burning conventional cigarettes [56]. The IQOS aerosol exerted a weaker biological impact on human organotypic bronchial epithelial cells than cigarette smoke at similar nicotine concentrations [57].…”
Section: Evidence From the Experimental Animal And Cellular Studiesmentioning
confidence: 94%
“…4 There have been some reported benefits from using E-cigarettes compared with conventional cigarettes, with potentially lower risk factors for cardiovascular disease in E-cigarette vapors versus tobacco smoke. 5 These effects are controversial and are countered by reports citing ill effects of the soluble components of E-cigarette vapor on endothelial barrier function promoting inflammation. 6 Animal studies have suggested that aerosol ingestion of E-cigarettes is safer than that of traditional cigarette smoke.…”
mentioning
confidence: 99%